Imprensa e Educação: um estudo histórico da educação na sociedade paranaense através da Revista Clube Curitibano no final do século XIX e início do século XX (1890-1912) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
The present research presents a historical study of the social, political and cultural movements, lived in Brazil, more specifically, in Curitiba, articulated by the press, through the republican ideals present in the passage of the 19th century to the 20th century, in the Revista Clube Curitibano , during the period (1890-1912) represented by the discourses of the intellectual collaborators of the magazine, who were representatives of the literate elite of the time in the capital of Paraná and responsible for disseminating their ideas, contributing to the formation of Curitiban society. Therefore, this study aims to analyze the evolution of Paraná's educational thinking materialized through these discourses disseminated in the magazine and to identify the ideological principles that underlie the proposal of public instruction and education in Paraná. For this, we adopted as a method, the epistemological posture of historical materialism, supported by the writings of Karl Marx and Friedrich Engels, through the categories of contradiction, totality and ideology. To carry out the research, which is documentary and bibliographic in nature, we carried out the state of knowledge, which took place in order to continue the research related to the central themes of our research: press, Clube Curitibano, ideology, intellectuals, history of education, since we are talking about a dynamic and continuous area of knowledge, with the objective of mapping and integrating the works carried out in this area of knowledge. Our time frame, part of the prints from 1890 to 1912, corresponds to the publications of “Revista Clube Curitibano”. After 1912, this magazine took a break, returning to circulation in 1932 We also obtained, from the Club's librarian and from the historian of the Project Memória da Sede Concórdia do Clube Curitibano, the history of the foundation of the Club, some news about it, within the our time frame and by Jornal O Dezenove de Novembro, and some copies of commemorative editions of the magazine (1932, 1950, 1962, 1985 and 1996), which bring a rescue of the history of the association and the magazine. Together with the reading and filing of all editions of the “Revista Clube Curitibano”, trying to map the main published themes and data about the editors and authors in the context of the Magazine and education. Subsequently, we sought information from other sources that helped us to analyze the ideas and their relationship with the interior of the economic, political and cultural situation in Brazil.
Keywords: Revista Clube Curitibano; Ideário Republicano; Imprensa – Paraná; Educação – Paraná; Clube Curitibano Magazine; Republican Ideas; Paraná press; Paraná education; CNPQ::CIENCIAS HUMANAS::EDUCACAO